Empowerment Digital Marketing Strategy One Time Entrepreneur Micro Application Social Media in the Village Mekar Jaya, District Sukmajaya, Depok City - Sri Yulianti; Sakti Brata Ismaya; Titus Indrajaya; Maya Sova; Eros Rosmiati (East Asian Journal of Multidisciplinary Research, 2023)
In the era of globalization, business competition is increasing rapidly and people's economic problems are also increasingly complex, so the right steps can be taken by a digital marketing strategy by empowering micro-scale businesses based on digitizing the creative economy in society to overcome post-pandemic economic problems. This research is an effort to empower micro-scale business actors. The research objective of this community service is one of the government's programs to accelerate the economy by conducting training and outreach as a whole to the wider community to all corners of the village or sub-district regarding the ease of macro-scale business for MSME actors, always active in government and private programs and universities to support increase in micro-scale income, for MSME business actors to consistently switch business patterns from analog to digital systems both through social media application platforms and websites to optimize facilities in the times.